Knowledge management framework for Malaysian small and medium size enterprises (SME) - Hamzah, Niza Adila (2004)
This paper reports the extent that Malaysian SMEs’ perceived awareness of knowledge management can be linked to six factors drawn from the theory and practice of knowledge management.These factors are: the balance between the need for knowledge and the cost of knowledge acquisition; the extent to which knowledge originates in the external environment; the internal knowledge-processing factory; internal knowledge storage; the use and deployment of knowledge within the organisation; and attention to human resources in knowledge processes.These six factors are compared with the results from a pilot study on the perceived awareness of local SMEs towards knowledge management.The intention is to provide guidance to local SMEs, on what can be effectively applied in their organisations based on their responsiveness towards knowledge management.The results suggest that local SMEs greatest need right now is to build, maintain and use effective and cost efficient knowledge repositories.It must be designed involving the user of the system and be integrated into SMEs everyday practice.In addition, a certain level of empowerment, formal and informal communication, and management commitment are also essential in encouraging the culture of knowledge sharing among SMEs.